The Influence of Viral Marketing, Flash Sales, and FOMO on Impulsive Buying of Skintific Products - Wahyuni, Sri; Vania, Amelindha (Ekonomi Bisnis, 2023)
Skintific is a beauty product from Canada that has introduced its products since 2021. This beauty brand offers effective solutions to strengthen the skin barrier and overcome various skin problems through its superior products. This research aims to determine the influence of Viral Marketing, Flash Sales, and FOMO on impulse purchases of Scientific products. The population of this study is GenZ on the island of Java. The sampling technique used is purposive sampling, which is a technique that gives researchers the freedom to select samples based on certain criteria. The sample collected amounted to 92 respondents. The method used is quantitative research with descriptive statistical analysis methods and processed using PLS-SEM 4. The results of this research show that viral marketing has an insignificant positive influence on impulse purchases, Flash Sale has an insignificant positive influence on impulse purchases, and FOMO has a significant positive influence on impulse purchasing of Scientific products.